TRANSFORMATOIN OF THE CADASTRE SYSTEM: SINSE THE INDEPENDENCE OF UKRAINE TO THE PRESENT - Жмур, Наталія Володимирівна; Лавренчук, Марина Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: comprehensively study the historical aspects of the land plots cadastral system development in Ukraine. Research methods: documentary analysis and synthesis, comparative analysis, historical, cognitive-analytical, etc. Results: carried out a historical analysis of the becoming and development of the cadastre system on Ukraine`s territory, and the theoretical provisions for maintenance of the registry has also been studies, its concepts and purposes are revealed. Discussion: clarified the normative consolidation of land cadastral accounting in the legislation of Ukraine, the practical aspect of the land cadastre maintaining in Ukraine. Since the independence of Ukraine, and the beginning of land reform, the process of privatization, purchase and sale, lease of land sales, a new stage of state has begun. After decades or moratorium on land sales, a new stage of land reform is beginning in Ukrainian legislation – the introduction of the land market, which will be regulated by the Law of Ukraine «On amendments to certain legislative acts of Ukraine on agricultural land circulation», adopted by Verkhovna Rada of Ukraine on March 31, 2021 year, and comes into force on July 1, 2021. Currently, in the conditions of improving the economic mechanism, the state faces the task of resolving the issue of improving land management, land valuation, improvement of existing technologies of land cadastre and introduction of new ones, as well as the use of the land cadastral accounting information. That`s why, the actualization and systematization of geospatial data, as well as establishment of new systems for improving cadastral system officiency is first priority task.